Image overlay surgery attempt of spinal dysraphism - Ito, Miiko; Kikuchi, Shigeru; Gando, Takeru; Sasaki, Kosuke; Tanaka, Masahiro; Abiko, Akihiro; Sonoda, Yukihiko (Nervous System in Children, 2023)
Confirming the level of the spinal cord is critical in spine surgery. However, in cases of severe spinal deformity, the surface merkmal deviates, reducing the usefulness of the intraoperative support system. Minimally invasive surgery, particularly in abdominal surgery, has grown in popularity in recent years. Complications caused by disorientation, on the other hand, are concern. As a result, image overlay surgery (IOS), which projects a three-dimensional image onto the body’s surface, has been used and proven to be effective. We used IOS to confirm the level of the spinal cord during surgical procedure for spinal dysraphism with severe deformity.